Proposta de uma infraestrutura de baixo custo com multiprocessamento e utilizando software aberto - Silva, Everaldo Lopes (2012)
This dissertation has the objective of identifying the technical aspects that deal with the utilization of computer cluster, specially the platforms with Linux operational system. It will be presented some cluster models in Linux, recognizing its advantages and its disadvantages and finally indicating the chosen model with the due justification. As part of this work, we will propose a laboratory with a cluster of two equipments connected with two gigabit interfaces each one and one computer working stand-alone. It will run Artificial Intelligence and Digital Design programs in this cluster, comparing its performance with only one computer running the same programs. The measuring and analysis will indicate if the Linux cluster would be a feasible infrastructure in technical and financial terms for AI and Digital Design application. The research method will be naturally the experimental and the approach method will be inductive, for through the results of the experimentation and technical analysis, it will be able to apply the knowledge achieved in others similar environments. For putting the experimental activity in the correct context, it will be used the more significant and contemporary research theories to establish in a clear way the scientific approach that it will lead the whole work